If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + 3) = 42 Reorder the terms: 3(3 + b) = 42 (3 * 3 + b * 3) = 42 (9 + 3b) = 42 Solving 9 + 3b = 42 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3b = 42 + -9 Combine like terms: 9 + -9 = 0 0 + 3b = 42 + -9 3b = 42 + -9 Combine like terms: 42 + -9 = 33 3b = 33 Divide each side by '3'. b = 11 Simplifying b = 11
| (x^2)-x+400=0 | | 2(a-3)=40 | | 0.34=lnx | | 6x-1=125 | | 2+x+3x=34 | | y=x(x-2y)+2y(x+2y) | | -4x^2+11x-6=o | | (x^2)-x+20=0 | | 16q-18=qr+t | | 5x+6-x=-30 | | 0.5x+7=-9 | | G-24=14 | | x^3-12x^2+230.4=0 | | 25+4y=25+16 | | 5x-3(x-3)=4+5x-8 | | 0.5x+6=17 | | -4(6x-7)=-24x-28 | | -12x-65=-7x | | 5-(2x+2)=-(-3x+5)-x | | 3(-2x+5)=9 | | 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 | | 7(-1x+5)=-7 | | x^2-2+3x+8=180 |